Hubungan Kemampuan Visual dengan Mobilitas Leher pada Anak Cerebral Palsy - Naufal, Adnan Faris; Lutfi, Idvan; Rahman, Farid; Pristianto, Arif; Kurniawan, Arif (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Background : Cerebral palsy causes limited activity and is often accompanied by cognitive impairment or visual deficits. Children with CP have unstable eye movements, associated with low neck muscle tone and low alertness as a result of which they produce low postural tone. Objective : To determine the relationship between visual ability and neck mobility in children with cerebral palsy. Methods : The research method used is observational with a cross sectional approach that emphasizes the observation or measurement of data once at a time. Results : Correlation test with Pearson product moment obtained a significance value (p) less than 0.05 (0.000 < 0.05) with an rxy value of 0.717. Conclusion : Ha is accepted, so it is concluded that there is a strong relationship between visual ability and neck mobility in Cerebral Palsy children.